Implementation of Story-Based Learning Methods to Improve Students' Understanding of the Stories of the Prophets and Apostles at SD Negeri 1403 Tiga Serangkai - Lelasari; Nasution, Jusri (Journal of Indonesian Primary School, 2024)
Islamic Religious Education plays an important role in shaping the character and morals of students from an early age, especially in understanding the stories of the Prophets and Apostles as role models in life. However, learning the stories of the Prophets and Apostles in Elementary Schools is often less interesting, causing students to have difficulty understanding and remembering the material. This study aims to improve the understanding of grade III students of SDN 1403 Tiga Serangkai towards the stories of the Prophets and Apostles through story-based learning methods. This study uses Classroom Action Research (CAR) with the Kemmis & McTaggart model, which includes four stages: planning, implementation, observation, and reflection. The subjects of the study were grade III students of SDN 1403 Tiga Serangkai. Data were collected through observation, interviews, evaluation tests, and documentation. Data analysis was carried out descriptively qualitatively and quantitatively to assess the increase in students' understanding before and after the application of the story method. The results showed that the story-based learning method significantly improved students' understanding. The average student test score increased from 67.5 in cycle I to 85.3 in cycle II. In addition, students were more enthusiastic, active, and easily remembered the stories and values ​​contained in the material. Thus, the story method can be an effective alternative in improving students' understanding of the stories of the Prophets and Apostles.